Features of intellectual functions inhibition among Ukrainian boxers: A sociocultural study - Ivanchenko, Andreyanna; Timchenko, Olexander; Zamperini, Adriano; Testoni, Ines; Gant, Olena; Malyk, Iaroslava (European Journal of Mental Health, 2020)
The effects of boxing’s extreme aggressive conditions in training and competitive activity in sportsmen’s mental working capacity still remains under-explored. While the neurophysiological effects caused by micro traumas to the brain have been extensively studied, less attention has been paid to the psychological consequences. This article reports on our study of the features of mental operations efficiency in Ukrainian boxers. The study involved athletes (n = 168, gender: men, average age: 25.5 ± 6.2 years), who were engaged in boxing and kickboxing in the Ukraine’s eastern region. A ‘Classification’ method was used: a set of 70 cards with the images of various objects, plants, and living beings was given with instructions to arrange the items into groups in such a way that the objects in each concrete group possess common properties. Athletes were divided into groups, depending on the level of their sport qualification. Adopting the Vygotskian perspective, this study shows correlations between the productivity of boxers’ thinking processes and the level of their sport skills: highly qualified sportsmen have many more well-marked thinking process defects than the sportsmen of the 2nd and 3rd categories. We observed a decrease in the generalization level, reduction in speed, deterioration of neurodynamic characteristics and criticality processes nearly in all participants. Exhaustibility and decrease in mental working capacity, impulsiveness of thinking, and its unproductive transformation were marked more often among the highly skilled boxers. A discussion on the cultural redefinition of this sport and on the necessary rehabilitative treatments is then presented.